Author Correction: Avian Influenza H5N6 Viruses Exhibit Differing Pathogenicities and Transmissibilities in Mammals - Zongzheng Zhao (Nature Portfolio, 2018)
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.